2014
DOI: 10.1002/jqs.2693
|View full text |Cite
|
Sign up to set email alerts
|

Environmental dynamics and luminescence chronology from the Orlovat loess-palaeosol sequence (Vojvodina, northern Serbia)

Abstract: The Carpathian Basin contains some of the best preserved loess deposits in Europe, including some of the continent's longest and best resolved climate records. Large areas of the basin have been intensively investigated in recent years, although deposits in the east remain largely unstudied, despite considerable regional variation in climate records. Here we discuss the sedimentary record exposed in the Orlovat brickyard using detailed litho‐ and pedo‐stratigraphic, enviromagnetic parameters and luminescence d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 52 publications
3
28
0
1
Order By: Relevance
“…Thus the youngest loess layer, V-L1L1, would have accumulated during the upper last glacial period and V-S0 formed during the Holocene. The lithostratigraphical and chronological analysis of the črvenka profile [9] were published in other studies [27,[30][31][32].…”
Section: Paleoecological Results Of the čRvenka Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Thus the youngest loess layer, V-L1L1, would have accumulated during the upper last glacial period and V-S0 formed during the Holocene. The lithostratigraphical and chronological analysis of the črvenka profile [9] were published in other studies [27,[30][31][32].…”
Section: Paleoecological Results Of the čRvenka Profilementioning
confidence: 99%
“…The MZ2 developed between 9.5 and 7.7 m. Based on the chronological data [27,[30][31][32] and Granaria frumentum (Fig. 5).…”
Section: Unauthenticatedmentioning
confidence: 98%
“…Generally, LPS have been investigated intensively in Southeastern Europe, but only some were OSL-dated in high-resolution (Constantin et al, 2014;Fitzsimmons and Hambach, 2014;Fuchs et al, 2008;Marković et al, 2014;Murray et al, 2014;Schmidt et al, 2010;Stevens et al, 2011;Zeeden et al, in press); mainly data concerning physical/chemical properties have been reported. Marković et al (2015) give an extensive overview.…”
Section: Stratigraphical Implicationsmentioning
confidence: 99%
“…Global climate change initiates spatially and temporally diverse regional terrestrial responses. The precise timing of climatic terminations does not necessarily occur coevally with the dated boundaries of loess and palaeosol units (Stevens et al, 2008;Marković et al, 2014c). This complicates the assignment of uniform stratigraphic schemes over wide areas at stadial-interstadial levels.…”
mentioning
confidence: 99%